Artery Bypass - Aronow, Wilbert S. (IntechOpen, 2013)
The latest diagnostic and therapeutic modalities in the management of coronary artery disease by coronary artery bypass graft surgery and by percutaneous coronary intervention with stenting and in the interventional management of other atherosclerotic vascular disease have led to a reduction in cardiovascular mortality and morbidity. This book entitled Artery Bypass provides an excellent update on these advances which every physician seeing patients with atherosclerotic vascular disease should be familiar with. This book includes 27 chapters written by experts in their topics.